US Army Corps of Engineers Archaeological Collections Condition Assessment - US Army Corps of Engineers Mandatory Center of Expertise for the Curation and Management of Archaeological Collections, St. Louis District (the Digital Archaeological Record)
The U.S. Army Corps of Engineers (USACE) is responsible for the management of thousands of cultural resources on Corps property and for the curation of millions of archaeological and historical resources removed from these lands. As mandated by federal regulation, agencies are required to ensure that all recovered archaeological materials and the associated records are adequately curated and are accessible for use by the Native Americans, public, and researchers. Unfortunately, funding shortfalls, lack of consistent national policy, and the magnitude of the problem have prevented compliance in many instances. USACE collections are public property, the result of many years of archaeological research and the expenditure of millions of federal dollars. A federally sponsored mitigation program usually provides for the recovery of materials from archaeological sites, the analysis of recovered items, the publication and circulation of a final report, and, sometimes the placement of collections in storage facilities for preservation, display, or future study. In the past, federal agencies afforded little attention to the maintenance of collections once salvage programs were completed. Through the years most collections have been stored free of charge by universities and museums. Inadequate funding and failing facilities now seriously hinder these institutions’ ability to adequately care for collections. The result has been a steady deterioration of both artifact and record collections to the point that the research and education value of many of these collections has become severely reduced. Additionally, many of the associated records have become separated from the artifacts, and some of the collections have been misplaced due to the lack of managed care and inadequate storage facilities. At the conclusion of the assessments for the Archaeological Collections Condition Assessment Project, the St. Louis District contacted over eight hundred facilities to inquire about USACE archaeological artifact and record collections. In total, one hundred sixty-six (166) facilities currently hold USACE archaeological collections, and another 18 are believed to house small, unconfirmed USACE collections. In order to meet mission requirements to conduct fieldwork within one year, existing curation needs assessment already conducted by several districts were used to provide some assessment data. Site visits were made to collect data for all other facilities that housed over 10 cubic feet of material and mail surveys were sent to those holding less than 10 cubic feet. In all, 119 facilities in 38 states were visited by St. Louis District personnel, or its representatives, in Fiscal Year 1998 to obtain detailed information regarding archaeological collections size, content, and current condition. Data resulting from existing reports, surveys, and site visits indicate that there are 166 facilities in 44 states that hold an estimated 46,522 cubic feet of artifact collections and 3,511 linear feet of record collections that are believed to fall under the curatorial responsibility of USACE within the United States (See Table 1 for a Division/District summary).